2018
DOI: 10.3390/rs10091434
|View full text |Cite
|
Sign up to set email alerts
|

Sea Surface Temperature (SST) Variability of the Eastern Coastal Zone of the Gulf of California

Abstract: The coastal zones are areas with a high flow of energy and materials where diverse ecosystems are developed. The study of coastal oceanography is important to understand the variability of these ecosystems and determine their role in biogeochemical cycles and climate change. Sea surface temperature (SST) analysis is indispensable for the characterization of physical and biological processes, and it is affected by processes at diverse timescales. The purpose of this work is to analyze the oceanographic variabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 38 publications
0
19
0
4
Order By: Relevance
“…Previous studies have focused on investigations of the warm pool variabilities on multiple time scales and the related atmospheric and oceanic processes [13][14][15][16][17][18]. For instance, surface heat flux, SST, 20 • C isotherm depth, upper ocean heat content, sea surface salinity, warm pool centroids and edges and many other properties of the warm pool were constantly studied [3,4,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused on investigations of the warm pool variabilities on multiple time scales and the related atmospheric and oceanic processes [13][14][15][16][17][18]. For instance, surface heat flux, SST, 20 • C isotherm depth, upper ocean heat content, sea surface salinity, warm pool centroids and edges and many other properties of the warm pool were constantly studied [3,4,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, Robles-Tamayo et al [36] reported a spatial and temporal variation of the SST along the coast of the GC. Their descriptive analysis of SST series showed that the values decreased from south to north, and the amplitude of the warm period decreased from south to north (the cold period increased from south to north).…”
Section: Introductionmentioning
confidence: 93%
“…Therefore, for the development of the environmental and oceanographic analyses in the mainland continental coast of the GC, the cluster analysis obtained by Robles-Tamayo et al [36] was used where four regions were determined with similar environmental characteristics based on the monthly SST data. Once the four regions were determined, the data analysis was performed through an analysis graph of the monthly and annual Chl a variability with time series and annual cycle plots, respectively.…”
Section: Processing Chlorophyll a Datamentioning
confidence: 99%
“…Previous use of satellite SST to monitor the coastal ocean have been carried out in different regions worldwide, e.g., the English Channel [21], Canada [22], Caribbean Sea [23], Argentina [24], South Africa [18], China [7], Western Australia [25][26][27][28], the Mediterranean Sea [29,30], and the Gulf of California [31]. The aforementioned studies used several satellite SST products including Moderate Resolution Imaging Spectroradiometer (MODIS) Aqua [22][23][24]26,30,31], MODIS Terra [18,22,23,26,30] and Advanced Very High Resolution Radiometer (AVHRR) [7,18,21,[25][26][27][28][29]31]. Some studies performed in the coastal zones are close to places of anthropogenic infrastructures such as aquaculture [22] or nuclear power stations [7].…”
Section: Introductionmentioning
confidence: 99%
“…Data acquisition and data processing of coastal satellite SST measurements are also prone to various error sources, e.g., cloud contamination, atmospheric correction errors, sampling errors, surface emissivity, sea surface roughness, and suspended particulate matter (SPM) [31,32]. This is a result both of the variable natural characteristics of the coastal zone [33] and of the poor network of near-shore coastal ocean instruments [18] when compared to the platforms in the open ocean [34].…”
Section: Introductionmentioning
confidence: 99%